2017
DOI: 10.1186/s13099-017-0168-y
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of intestinal and systemic sequelae of murine Campylobacter jejuni infection by probiotic VSL#3 treatment

Abstract: BackgroundThe incidence of human Campylobacter jejuni infections is progressively increasing worldwide. Probiotic compounds might open up valuable tools to decrease pathogen burden and subsequent pro-inflammatory immune responses, but in vivo data are scarce.Methods and resultsSecondary abiotic mice generated by broad-spectrum antibiotic treatment were perorally challenged with the commercial probiotic compound VSL#3 consisting of Streptococcus thermophilus, Bifidobacterium breve, Bifidobacterium longum, Bifid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…One major reason for these severe immunopathological responses mounting in acute ulcerative enterocolitis is the absence of colonization resistance and the lack of IL-10 providing murine resistance to C. jejuni LOS [38,39]. In consequence, C. jejuni infected IL-10 -/mice display pronounced LOS induced and TLR-4-dependent innate and adaptive immune responses that are not restricted to the intestinal tract, but can also be observed in extra-intestinal including systemic compartments [19,30,[40][41][42][43][44][45][46]. Based on the results of this study, we therefore plan to include more C. coli strains from different sources (environmental, animal, human) in our future in vivo infection studies.…”
Section: Discussionmentioning
confidence: 99%
“…One major reason for these severe immunopathological responses mounting in acute ulcerative enterocolitis is the absence of colonization resistance and the lack of IL-10 providing murine resistance to C. jejuni LOS [38,39]. In consequence, C. jejuni infected IL-10 -/mice display pronounced LOS induced and TLR-4-dependent innate and adaptive immune responses that are not restricted to the intestinal tract, but can also be observed in extra-intestinal including systemic compartments [19,30,[40][41][42][43][44][45][46]. Based on the results of this study, we therefore plan to include more C. coli strains from different sources (environmental, animal, human) in our future in vivo infection studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have been conducted using cell cultures or mouse models. [81][82][83][84] These studies demonstrated probiotic products, such as Bacillus and Lactobacillus, reduced Campylobacter colonization in mice, C. jejuni invasion into cultured human epithelial cells, or release of pro-inflammatory cytokines from Campylobacter-infected cells. Since chicken is a major reservoir for Campylobacter, there have been active efforts in developing probiotics to reduce Campylobacter colonization in poultry.…”
Section: New and Non-antibiotic Approaches To The Control Of Campylobmentioning
confidence: 99%
“…Very recently, we were able to demonstrate the extensive impact of VSL#3 treatment on mucosal, peripheral, and systemic innate and adaptive immunity exerting beneficial anti-inflammatory effects in intestinal as well as systemic compartments of mice that had been subjected to broad-spectrum antibiotic treatment [ 27 ]. In addition, VSL#3 treatment was sufficient to attenuate intestinal, but also extra-intestinal including systemic pro-inflammatory responses upon murine infection with the enteropathogen Campylobacter jejuni [ 35 ].…”
Section: Discussionmentioning
confidence: 99%